Avaliação psicossocial e hemodinâmica de atletas de boxe em situação pré-competitiva e de treino - Alejo, Andres Armas (2019)
Introduction: The current dissertation was divided into two studies. Study 1, Objective: Analyze the effect of the anxiogenic parameters in male boxing athletes. Method: Nine-five male athletes participated in the study (60 juveniles and 35 adults). The juveniles group was compound by 38 non-medalists (Juv-NM Group) and 22 medalists (Juv-Med Group) with mean age 17.5 ± 0.50 years. The adults group (athletes over 18 years old) was compound by 11 non-medalists (Adul-NM Group) and 24 medalists (Adul-Med Group). The CSAI-2 anxiety questionnaire was used to determinate pre completive levels of cognitive, somatic anxiety and self-confidence. Results: Both groups Group-NM and Group-Med were classified as low cognitive anxiety levels (15.92 ± 5.20 and 12.77 ± 2.62, respectively), and for somatic anxiety levels (14.03 ± 4.6320 and 12.55 ± 2.46, respectively), with a high self-confidence levels of 29.42 ± 4.82 (Group-NM) and 31.59 ± 4.24 (Group-Med), indicating a significant difference only in cognitive anxiety levels. Study 2, Objective: Evaluate post-training effects on hemodynamic and recovery indicators in boxing athletes. Methodology: Eight male boxing athletes (age: 23 ± 3.83 years, height: 1.75 ± 0.09 cm, body weight: 68.43 ± 12.51 kg); with minimum sport experience of 12 months. The subjects were submitted a 120 minutes of single training session following by three different recovery protocols: Passive Recovery (RP), Dry Needling (DN) and Cold Water Immersion (CW). Hemodynamic indicators were evaluated before, immediately after, with 5', 10', 20', 30', 40', 50', and 60' after training session. Results: Systolic blood pressure and heart rate were the most significant in the post-exercise period when compared to the rest period (pre-exercise) and after recovery, (P <0.05). Conclusion: Study 1 indicates self-confidence may interfere with anxiety levels, considering that medal boxers shown less cognitive anxiety levels than non-medalists, furthermore both groups present high self-confidence levels. Study 2 indicates that the use of three different types of post-training recovery protocols can modulat